Several Appropriate Statistical Techniques in Research - Subedi, Shantiram (Damak Campus Journal, 2023)
This paper has the main purpose to assist researchers and students in choosing the appropriate statistical test for studies that examine one variable or more variables. The aim of this article is to consider the role which statistical methods can sensibly take in some relevant fields. Other objective of writing this paper is to provide the algorithm of choosing the statistical techniques in the data analysis. This article is concentrated to define data analysis and the concept of data preparation. Then, the data analysis will be discussed. The article covers a brief outline of the variables, an understanding of quantitative and qualitative variables and measure of central tendency. This article will also try to apprise the reader with the basic research techniques that are utilized while conducting various studies. Finally, there is a focus on parametric and nonparametric tests for data analysis and various strategies in this concept.